Dehydrocostus lactone inhibits cell proliferation and induces apoptosis by PI3K/Akt/Bad and ERS signalling pathway in human laryngeal carcinoma. Issue 11 (21st April 2020) - Zhang, Ren; Hao, Ji; Wu, Qingming; Guo, Kaiwen; Wang, Chao; Zhang, Wei Kevin; Liu, Wanxin; Wang, Qiang; Yang, Xinzhou
Abstract: The anti‐cancer effect of dehydrocostus lactone (DHL) derived from Saussurea costus (Falc.) Lipech against laryngeal carcinoma was assessed. The cytotoxic activity of DHL against laryngeal carcinoma is still obscure. Therefore, our study investigated the role of DHL in the growth inhibition of laryngeal carcinoma in vitro and in vivo,  and the molecular mechanism of DHL‐induced apoptosis in cancer cells of the larynx. The results showed that DHL inhibits the viability, migration and proliferation of Hep‐2 and TU212 cells with little toxic effects on human normal larynx epithelial HBE cell line. Flow cytometry analysis (FAC) analysis and staining assay (Hoechst 33258) indicated that DHL stimulated Hep‐2 and TU212 cell apoptosis in a dose‐dependent manner. Mechanistically, DHL is capable of inhibiting Hep‐2 and TU212 cell viability via promoting p53 and P21 function, meanwhile DHL dose‐dependently induces Hep‐2 and TU212 cells apoptosis via activating mitochondrial apoptosis by inhibiting PI3K/Akt/Bad pathway and stimulating endoplasmic reticulum stress‐mediated apoptosis pathway. In vivo, DHL inhibited the growth of the Hep‐2 nude mouse xenograft model and observed no significant signs of toxicity in the organs of nude mice. In vivo experiments further confirmed the anti‐cancer effect of DHL on laryngeal carcinoma cells in vitro, and DHL‐treated nude mice can reduce the volume of tumours. Together, our study indicated that DHL has the potential to inhibit human laryngeal carcinoma via activating mitochondrial apoptosis pathway by inhibiting PI3K/Akt/Bad signalling pathway and stimulating endoplasmic reticulum stress‐mediated apoptosis pathway, providing a strategy for the treatment of human laryngeal carcinoma.